Laparoscopic cholecystectomy in super elderly ( 90 years of age) (2023)
Background Nonagenarian patients are an age group in progressive growth. In this age group, indications for surgical procedures, including cholecystectomy, will be increasingly frequent, as biliary pathology and its complications are frequent in this population group. The main objective of this study was to analyze the safety and outcomes of laparoscopic cholecys- tectomy in patients older than 90 years. Methods A retrospective observational cohort study was designed. This study involved 600 patients that were classified in 4 age groups for analysis (under 50 years, 50–69 years, 70–89 years, and over 90 years). Demographic, clinical, paraclinics, surgical, and outcome variables were compared according to age group. A multivariate analysis, which included variables considered clinically relevant, was performed to identify factors associated with mortality and complications classified with the Clavien–Dindo scale. Results The patients evaluated had a median age of 65.0 (IQR 34.0) years and there was a female predominance (61.8%). A higher complication rate, conversion rate, subtotal holecystectomy rate, and prolonged hospital stay were found in nonagenarians. The overall mortality rate was 1.6%. Mortality in the age group over 90 years was 6.8%. Regression models showed that age over 90 years (RR 4.6 CI95% 1.07–20.13), presence of cholecystitis (RR 8.2 CI95% 1.29–51.81), and time from admission to cholecystectomy (RR 1.2 CI95% 1.10–1.40) were the variables that presented statistically significant differences as risk factors for mortality. Conclusion Cholecystectomy in nonagenarian patients has a higher rate of complications, conversion rate, subtotal cholecystectomy rate, and mortality. Therefore, an adequate perioperative assessment is necessary to optimize comorbidities and improve outcomes. Also, it is important to know the greatest risk for informed consent and choose the surgical equipment and schedule of the procedure.